2012
DOI: 10.1186/gb-2012-13-7-r64
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis pan-genome sequence analysis reveals diversity of skin commensal and hospital infection-associated isolates

Abstract: BackgroundWhile Staphylococcus epidermidis is commonly isolated from healthy human skin, it is also the most frequent cause of nosocomial infections on indwelling medical devices. Despite its importance, few genome sequences existed and the most frequent hospital-associated lineage, ST2, had not been fully sequenced.ResultsWe cultivated 71 commensal S. epidermidis isolates from 15 skin sites and compared them with 28 nosocomial isolates from venous catheters and blood cultures. We produced 21 commensal and 9 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
201
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(233 citation statements)
references
References 49 publications
30
201
1
1
Order By: Relevance
“…The capABCD operon is involved in resistance to neutrophil phagocytosis (8). Finally, in a pangenomic study of S. epidermidis, it was suggested that isolates having a formate dehydrogenase-encoding gene (fdh) were characterized by a reduced virulence and that this gene was lost in virulent strains (21). This is consistent with our study, as strain CSUR P278 lacked the fdh gene.…”
supporting
confidence: 88%
“…The capABCD operon is involved in resistance to neutrophil phagocytosis (8). Finally, in a pangenomic study of S. epidermidis, it was suggested that isolates having a formate dehydrogenase-encoding gene (fdh) were characterized by a reduced virulence and that this gene was lost in virulent strains (21). This is consistent with our study, as strain CSUR P278 lacked the fdh gene.…”
supporting
confidence: 88%
“…Such markers may promote a hospital lifestyle and thus provide increased opportunities to cause infections. In contrast, the genetic markers fdh and arginine catabolic mobile element (ACME) have been reported to be more common in contaminant or commensal isolates than in true infection isolates (14)(15)(16).…”
mentioning
confidence: 99%
“…In addition, we assessed the role of the clonal complex-specific hsdS genes in the restriction barrier of S. epidermidis. For this purpose, we engineered DC10B cells, which can bypass the type IV restriction system, to encode a plasmid artificial modification (PAM) system (18) for type I HsdMS complexes of S. epidermidis strains, including NIH04008 (19), RP62A (20), NIH051475 (19), and VCU036 (21). NIH04008 belongs to CC2, the most common CC among clinical isolates, while RP62A is a CC10 laboratory-passaged strain, and the remaining two strains are clinical isolates belonging to CC89.…”
mentioning
confidence: 99%